Flavor, fragrance and odor analysis - Marsili, Ray , 1946- (Boca Raton, Florida : CRC Press, 2012)
"Emphasizing SBSE techniques alongside advances in mass spectrometry, sample preparation, gas chromatography (GC)-olfactometry, and electronic-nose technology, this new edition discusses the significant advantage of these methods for flavor and odor studies in the food, cosmetic, and pharmaceutical industries. Written from a practical, problem-solving perspective, it discusses the chemical structures of key flavor and fragrance compounds, contains numerous examples and chromatograms, and emphasizes novel solid-phase micro extraction procedures. It also presents important updates on GC-olfactometry as a tool for studying flavor synergy effects"-- Provided by publisher
"Sample preparation techniques for isolating and concentrating flavor and odor-active chemicals from foods prior to GC-MS analysis continue to evolve, providing lower detection limits while being more amenable to instrumental automation. Solventless extraction techniques like solid-phase microextraction (SPME) and stir bar sorptive extraction (SBSE) have wide application appeal and are now significant problem-solving tools for flavor and odor chemists. While the first edition of Flavor, Fragrance and Odor Analysis emphasized SPME, a newer technique at the time, this edition focuses on the advantages of SBSE, including sequential SBSE and other sample manipulation techniques that increase the sensitivity and application potential of this surprisingly simple but amazingly powerful technique"-- Provided by publisher
1. Sequential stir bar sorptive extraction -- 2. Selectable one-dimensional or two-dimensional gas chromatography-olfactometry/mass spectrometry -- 3. Simple derivatization prior to stir bar sorptive extraction to improve extraction efficiency and chromatography of hydrophilic analytes : Acylation of phenolic compounds -- 4. Analysis of musty microbial metabolites by stir bar sorptive extraction -- 5. The olfactometric analysis of milk volatiles with a novel gas chromatography-based method : A case study in synergistic perception of aroma compounds -- 6. Characterizing aroma-active volatile compounds of tropical fruits -- 7. On the synthesis and characteristics of aqueous formulations rich in pyrazines -- 8. Using automated sequential two-dimensional gas chromatography/mass spectrometry to produce a library of essential oil compounds and track their presence in gin, based on spectral deconvolution software -- 9. Character-impact flavor and off-flavor compounds in foods
Includes bibliographical references and index
Keywords: Food -- Sensory evaluation